Evolution of landscape pattern and ecological environment effect in Pudacuo National Park, China - He, Xuejuan; Zhang, Shunmin; Li, Xiaona; Ran, Kui; Chen, Yulin; Huang, Xiaoyuan (Frontiers in Environmental Science, 2025)
As an important part of China’s ecological security barrier on the plateau, the rational configuration of landscape patterns and a good ecological environment are crucial guarantees for the high-quality development of national parks. Using Landsat image data from 2000 to 2024, this study analyzes pudacuo national park as an example. The study uses Morphological Spatial Pattern Analysis (MSPA) to analyze the evolution characteristics of the landscape pattern and the Remote Sensing Ecological Index (RSEI) to evaluate the ecological environment quality(EEQ). In the meantime, the geodetector, bivariate spatial autocorrelation, and Spearman correlation coefficient were combined to investigate and ascertain the geographic relationship between the two. The results of the research indicate that: (1) the park’s core area is primarily forested and far away from populated regions, with high stability in its, Aggregation Index (AI) and Largest Patch Index (LPI); in the contrary, the edge area’s grassland and unused land are heavily impacted by human disturbances like grazing and tourism, and the landscape pattern is distinguished by fragmentation and degradation of ecological functions; (2) From 2000 to 2024, the ecological environment quality of pudacuo national park continued to improve. The ecological environment quality in the study area was mainly rated as “good,” accounting for up to 49.04% of the total, with the trend in ecological environment quality remaining “basically stable.” (3) Correlation analysis showed that ecological environment quality was significantly positively correlated with LPI, AI, and Patch Cohesion Index (COHESION). The spatiotemporal evolution of ecological environment quality in pudacuo national park is not only constrained by landscape fragmentation and core patch patterns but is also closely related to landscape diversity and overall spatial structure. This study aims to provide a scientific basis and decision support for the ecological civilization construction and sustainable development of pudacuo national park.